The food environment of Brazilian public and private schools - Ariene Silva do Carmo; Maíra Macário de Assis; Cristiane de Freitas Cunha; Tatiana Resende Prado Rangel de Oliveira; Larissa Loures Mendes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Abstract: This study's aim was to characterize the food environment of Brazilian public and private schools. This was a national school-based cross-sectional study with 1,247 schools - among which 81.09% were public and 18.91% were private - in 124 Brazilian municipalities. The data originated from the Questionnaire on Aspects of the School Environment, used in the Study of Cardiovascular Risk in Adolescents (ERICA) in 2013 and 2014. Data analysis was conducted in 2017. The chi-square test was used to compare proportions. A greater proportion of public schools offered school meals (98.15%) in comparison to private schools (8.07%) (p < 0.001). The internal sale of food and beverages was more prevalent in private schools (97.75% vs. 45.06%, p < 0.001). Also, sale and advertisement of processed and ultra-processed foods (sodas, cookies, savory snacks, sandwiches and pizza), as well as the presence of vending machines for industrialized products (18.02% vs. 4%) (p < 0.001) were more common in private schools. Street vendors at the school gate or surroundings were identified in 41.32% of the public schools and 47.75% of the private schools (p > 0.05). These findings reveal the predominance of obesogenic environments mainly in private schools, and can contribute to the design of Brazilian public policies to promote a healthy school food environment.